ANALISIS PARAMETER KINETIK DAN TRANSIEN TERAS KOMPAK REAKTOR RSG-GAS - Kuntoro, Iman; Pinem, Surian; Sembiring, Tagor Malem (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
For increasing the efficiency of fuel element of the RSG-GAS reactor, some alternative configuration has been searched to obtain a compact core configuration. Calculation result of the neutronics parameters that the compact core with insertion fuel element to all irradiation facility (IP) can increase operation cycle length to about 23.6 %. Then, it is necessary to calculate the kinetic parameters and transient analysis of the compact core to verify the reactor operation safety. Calculations were performed by means of WIMS/D4 and MTRDYN code for generation of cell diffusion constants and for kinetic parameters and transient analysis respectively. The result showed that the total delayed neutron fraction of compact core increases by 2 % and the prompt neutron lifetime decreases 8.3 % compared to the equilibrium core. Maximum temperature of the fuel element at transient at initial power of 1 W is 71.64 0C and at the power 1 MW is 126.60 0C. The result showed that the compact core of RSG-GAS reactor can be used as alternative core safely.